Exploring the Response of Combined Urban Sewer System to the Implementation of Green Roof. (August 2018) - Gao, Yuqin; Wang, Dongdong; Schmidt, A; Tang, Yun
Abstract: In order to find an efficient and reliable method for assessing the impact of green roofs on runoff in urban areas, IUHM-GreenRoof combination model is established via Matlab. Taking CDS-51 catchment located in Dolton, Illinois as a case, and considering different green roof coverage ratios as well as runoff conditions, the influence on the catchment outlet runoff because of the application of green roofs is analysed by running the model in two typical storms. The results show that green roofs have good water storage capacity, which can effectively decrease the catchment runoff in terms of peak discharge and volume. Moreover, the green roof coverage ratio has more influence on runoff than green roof runoff conditions.